Средневековое погребение из одиночного кургана в Котельниковском районе Волгоградской области. - Кривошеев, М.В.; Блохин, В.Г. (Степи Европы в эпоху средневековья, 2012)
В октябре 2006 г совместной экспедицией Волгоградского государственного университета и Областного научно-производственного центра охраны памятников истории и культуры Волгоградской области проводилис ь спасательные раскопки одиночного кургана у пос. им.Ленина Котельниковского района Волгоградской области The paper describes an inlet burial from a sing le barrow near Lenin settlement o f Kotelnikovskii reg ion in Volgograd province. Among the grave goods of the burial there is a temporal pendant with a biconical bead thread and con ic thorns. In historiography, burials with similar pendants were ambiguously dated back from the 12th to 14th century and attributed to the ethnoses of the Chiomyie Klobuki, the Polovtsy, and “Saksins”. The author substantiates the connection between the Lower Volga complex and burials of the Ros river area, which gives grounds to assume probable migration of the nomads, who were included in the Chiomyie Klobuki union, to the territory of the Volga region in the Golden Horde time.